PERAN KEPALA SEKOLAH DALAM PENDAMPINGAN GURU UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI SMKN 1 KARIMUNJAWA - Anita Nadzifah; Patto Prawansyah; Soedjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify the role of the principal in supervising teachers to improve the quality of learning at SMKN 1 Karimunjawa. With a qualitative approach and case study method, data were obtained through interviews, classroom observations, and documentation. The results show that the principal acts as a facilitator, mentor, and evaluator through classroom observations, feedback, and follow-up, thereby improving teachers' pedagogical competence. However, obstacles such as time constraints, differences in teacher competence, and resources are still faced. This study recommends strengthening support for principals and teachers, as well as increasing resources to optimize supervision.